ASR Enhances Environmental Stress Tolerance and Improves Grain Yield by Modulating Stomatal Closure in Rice - Park, Seong-Im; Kim, Jin-Ju; Shin, Sun-Young; Kim, Young-Saeng; Yoon, Ho-Sung (Frontiers in Plant Science, 2020)
Abscisic acid-, stress-, and ripening-induced (ASR) genes are involved in responding to abiotic stresses, but their precise roles in enhancing grain yield under stress conditions remain to be determined. We cloned a rice (Oryza sativa) ASR gene, OsASR1, and characterized its function in rice plants. OsASR1 expression was induced by abscisic acid (ABA), salt, and drought treatments. Transgenic rice plants overexpressing OsASR1 displayed improved water regulation under salt and drought stresses, which was associated with osmolyte accumulation, improved modulation of stomatal closure, and reduced transpiration rates. OsASR1-overexpressing plants were hypersensitive to exogenous ABA and accumulated higher endogenous ABA levels under salt and drought stresses, indicating that OsASR1 is a positive regulator of the ABA signaling pathway. The growth of OsASR1-overexpressing plants was superior to that of wild-type (WT) plants under paddy field conditions when irrigation was withheld, likely due to improved modulation of stomatal closure via modified ABA signaling. The transgenic plants had higher grain yields than WT plants for four consecutive generations. We conclude that OsASR1 has a crucial role in ABA-mediated regulation of stomatal closure to conserve water under salt- and drought-stress conditions, and OsASR1 overexpression can enhance salinity and drought tolerance, resulting in improved crop yields.